Catechol 1,2-Dioxygenase From Paracoccus sp. MKU1—A Greener and Cleaner Bio-Machinery for cis, cis-Muconic Acid Production by Recombinant E. coli - Aravind, Manikka Kubendran; Varalakshmi, Perumal; John, Swamidoss Abraham; Ashokkumar, Balasubramaniem (Frontiers in Bioengineering and Biotechnology, 2021)
Cis, cis-muconic acid (ccMA) is known for its industrial importance as a precursor for the synthesis of several biopolymers. Catechol 1,2-dioxygenase (C12O) is involved in aromatic compounds catabolism and ccMA synthesis in a greener and cleaner way. This is the first study on C12O gene from a metabolically versatile Paracoccus sp. MKU1, which was cloned and expressed in E. coli to produce ccMA from catechol. From the E. coli transformant, recombinant C12O enzyme was purified and found to be a homotrimer with a subunit size of 38.6 kDa. The apparent Km and Vmax for C12O was 12.89 µM and 310.1 U.mg-1, respectively, evidencing high affinity to catechol than previously reported C12Os. The predicted 3D-structure of C12O from MKU1 consisted of five α-helices in N-terminus, one α-helix in C-terminus, and nine β-sheets in C-terminus. Moreover, a unique α-helix signature ‘EESIHAN’ was identified in C-terminus between 271 to 277 amino acids, however the molecular insight of conservative α-helix remains obscure. Further, fed-batch culture was employed using recombinant E. coli expressing C12O gene from Paracoccus sp. MKU1 to produce ccMA by whole-cells catalyzed bioconversion of catechol. With the successive supply of 120 mM catechol, the transformant produced 91.4 mM (12.99 g/L) of ccMA in 6h with the purity of 95.7%. This single step conversion of catechol to ccMA using whole-cells reactions of recombinants did not generate any by-products in the reaction mixtures. Thus, the recombinant E. coli expressing high activity C12O from Paracoccus sp. MKU1 holds promise as a potential candidate for yielding high concentrations of ccMA at faster rates in low cost settings.